2020
DOI: 10.1371/journal.pone.0230220
|View full text |Cite
|
Sign up to set email alerts
|

High expression of Helicobacter pylori VapD in both the intracellular environment and biopsies from gastric patients with severity

Abstract: Helicobacter pylori is a Gram-negative bacterium that causes chronic atrophic gastritis and peptic ulcers and it has been associated with the development of gastric adenocarcinoma and mucosa-associated lymphoid tissue (MALT). One of the more remarkable characteristics of H. pylori is its ability to survive in the hostile environment of the stomach. H. pylori regulates the expression of specific sets of genes allowing it to survive high acidity levels and nutrient scarcity. In the present study, we determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 43 publications
(78 reference statements)
1
20
0
Order By: Relevance
“…Another report showed treatment of biopsy samples with chloramphenicol and kanamycin induced the expression of TAs. These suggested that vapD is a virulent factor, protects the bacterium by aiding biofilm formation [ 66 , 67 ]. It helps the bacterium to survive in a hostile environment.…”
Section: Discussionmentioning
confidence: 99%
“…Another report showed treatment of biopsy samples with chloramphenicol and kanamycin induced the expression of TAs. These suggested that vapD is a virulent factor, protects the bacterium by aiding biofilm formation [ 66 , 67 ]. It helps the bacterium to survive in a hostile environment.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the higher infection by coccoid forms of H. pylori in patients with GC, compared to patients with gastritis or gastric ulcer, had been mentioned by other researchers[ 57 ]. A number of studies have shown that coccoid forms of H. pylori retained urease activity[ 58 ] and the expression of such antigens as CagA, UreA, porin, components of the Cag type IV secretion system (TFSS), antigen-binding adhesin of the blood group BabA and others[ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A relevant increase was also found for the virulence-associated protein VapD (HP0967) by sera of patients with AIG (selection B). In a recent paper by Morales-Espinosa et al (2020) high level of expression of virulence-associated protein D (VapD) of H. pylori were outlined inside adenocarcinoma gastric (AGS) cells and in gastric biopsies from patients suffering from different HP-related diseases. They observed that VapD is only expressed in the bacterium as a consequence of its interaction with the host cells, suggesting that it might contribute to H. pylori persistence inside the gastric epithelial cells, being involved in the protection of the bacterium from the intracellular environment and in its growth rate reduction, as well as enabling long-term infection and treatment resistance.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that VapD is only expressed in the bacterium as a consequence of its interaction with the host cells, suggesting that it might contribute to H. pylori persistence inside the gastric epithelial cells, being involved in the protection of the bacterium from the intracellular environment and in its growth rate reduction, as well as enabling long-term infection and treatment resistance. However in their work Morales-Espinosa et al (2020) Did not test the reactivity of patients sera against VapD protein, they analyzed VapD expression in AGS cells in in vitro time course experiments and they tested the expression level of VapD by RT qPCR in 82 gastric biopsies from patients outlying high expression levels of this gene/protein in vivo in particular in association with follicular gastritis. Thus, in the light of this work we think that our finding related to an antibody response against VapD in patients can be considered promising for future validations.…”
Section: Discussionmentioning
confidence: 99%